2020
DOI: 10.1016/j.agwat.2020.106357
|View full text |Cite
|
Sign up to set email alerts
|

Soil water balance models for determining crop water and irrigation requirements and irrigation scheduling focusing on the FAO56 method and the dual Kc approach

Abstract: This study reviews soil water balance (SWB) model approaches to determine crop irrigation requirements and scheduling irrigation adopting the FAO56 method. The K c -ET o approach is discussed with consideration of baseline concepts namely standard vs. actual K c concepts, as well as single and dual K c approaches. Requirements for accurate SWB and appropriate parameterization and calibration are introduced. The one-step vs. the two-step computational approaches is discussed before the review of the FAO56 metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
55
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(81 citation statements)
references
References 178 publications
0
55
0
1
Order By: Relevance
“…A wide review on crop coefficients for trees and vines [14] has shown that the variability in K c values is large and much greater than the variability in K cb values, particularly by the end season, as well as in the initial and the late seasons, which results from rainfall events occurring during these periods. Aiming at ET partitioning [16], studies have been carried out based on soil evaporation, measured in mi-crolysimeters; actual crop transpiration, determined with sap flow sensors [5,17,18]; and/or actual crop evapotranspiration, obtained using eddy covariance techniques [4,19,20], as reviewed by Pereira et al [21]. A different approach that is currently used is remote sensing, namely, exploring the relationships between K cb act and a spectral vegetation index [22][23][24][25], which allows its use, together with ground data, in modeling [21].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A wide review on crop coefficients for trees and vines [14] has shown that the variability in K c values is large and much greater than the variability in K cb values, particularly by the end season, as well as in the initial and the late seasons, which results from rainfall events occurring during these periods. Aiming at ET partitioning [16], studies have been carried out based on soil evaporation, measured in mi-crolysimeters; actual crop transpiration, determined with sap flow sensors [5,17,18]; and/or actual crop evapotranspiration, obtained using eddy covariance techniques [4,19,20], as reviewed by Pereira et al [21]. A different approach that is currently used is remote sensing, namely, exploring the relationships between K cb act and a spectral vegetation index [22][23][24][25], which allows its use, together with ground data, in modeling [21].…”
Section: Introductionmentioning
confidence: 99%
“…Aiming at ET partitioning [16], studies have been carried out based on soil evaporation, measured in mi-crolysimeters; actual crop transpiration, determined with sap flow sensors [5,17,18]; and/or actual crop evapotranspiration, obtained using eddy covariance techniques [4,19,20], as reviewed by Pereira et al [21]. A different approach that is currently used is remote sensing, namely, exploring the relationships between K cb act and a spectral vegetation index [22][23][24][25], which allows its use, together with ground data, in modeling [21]. Properly calibrated models may be used to evaluate crop water requirements, to support proper irrigation management and to evaluate the impact of crops and management, even under the application of water deficit strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Citrus cultivation in China has been intensified with the use of large-area orchards [4]; at the same time, drip irrigation is widely applied in citrus growing. Therefore, the decision-making and scheduling of the irrigation of citrus orchards have become important problems [5]. The traditional drip irrigation operation depends mainly on subjective experience to make decisions and schedules and lacks an objective reference [6].…”
Section: Introductionmentioning
confidence: 99%
“…Evapotranspiration represents the simultaneous processes of transfer of water to the atmosphere by transpiration and evaporation in a soil-plant system (Allen et al 1998). In particular, reference evapotranspiration (ETo) is an important hydrological variable for irrigation water management and hydrological modeling (Immerzeel and Droogers 2008;Pereira et al 2020). Since the agricultural sector accounts for 70% of freshwater withdrawals (Kummu et al 2012) and around 90% of global freshwater consumption (Wada et al 2012), improved understanding of changes in evapotranspiration is essential for dependable projections of global freshwater availability under conditions of climate change.…”
Section: Introductionmentioning
confidence: 99%